KEJAHATAN LINGKUNGAN SEBAGAI KEJAHATAN INTERNASIONAL PADA MASA KONFLIK BERSENJATA BERDASARKAN HUKUM INTERNASIONAL (STUDI KASUS ICC-02/05: SITUATION IN DARFUR, SUDAN) - Revita Ernawati (BELLI AC PACIS, 2020)
This article examine the types of environmental crimes according to international law that occurred in Sudan during a non international armed conflict situation. The method of writing used in this legal research are statute approach, historical approach and conseptual approach. The environmental crime particularly as an international crime currently has no precise definition under international law. The prosecution of environmental crimes depend on national criminal law accordingly, whereas in the case of Sudan became difficult as the perpretrator is the controlling government. The question arises as to whether the environmental crimes that occured in Sudan can be categorized as international crimes based on the current existing threshold under international law. The result of this legal research shows that: First, environmental crimes that occured should be part of grave violations of humanitarian law, consisting of elements of actus reus and mens rea and have serious and severe impacts. Second, the Triple Cumulative Standard as the most common threshold of environmental destruction under humanitarian law will have several difficulties to be applied in this case. Third, the environmental crimes linked to the core crimes will have considerably more legal basis under international law rather than as a standalone crime.